Angiostrongylus costaricensis, a neotropical parasite with a controversial diagnosis and treatment. - Gutiérrez-Espeleta, Gustavo (2019)
Abdominal angiostrogyliasis is a sporadic parasitosis that occurs in Neotropical countries, mainly in Costa Rica. It is a disease with an infrequent diagnosis and a controversial treatment. We discuss a case of an adult that presents a severe generalized discomfort, abdominal pain and an intense eosinophilia that leads to the detection of a mass at the right lower quadrant. Definitive diagnosis is achieved by the Morera Test and the treatment includes the use of azythromicin and metronidazole: no antihelmintic drugs or surgery were used. The case shows that both the diagnosis and treatment of this parasitosis are uncertain. An important underreporting of the disease may occur, as well as confusion of the symptoms with other pathologies.